IL-17 Mildly Rescued the Impaired Proliferation of Alveolar Epithelial Cells Induced by LCN2 Overexpression - Tingting Lv; Ziliang Hou; Kaiyuan Yang; Jinxiang Wang (Canadian Respiratory Journal)
Introduction. The impaired proliferative capacity of alveolar epithelial cells after injury is an important factor causing epithelial repair dysfunction, leading to the occurrence of idiopathic pulmonary fibrosis (IPF). Alveolar type 2 (AT2) cells as the stem cells of alveolar epithelium participate in the repair process after alveolar injury. Lipocalin-2 (LCN2) participates in multiple processes regulating the pathological process of alveolar epithelial cells, but the mechanisms involved are still unclear. Method. We used a BLM-treated mouse model to characterize the expression of LCN2 in lung fibrosis regions and analyzed the location of LCN2 in alveolar epithelial cells. Moreover, human pulmonary alveolar epithelial cells (HPAEpiCs) were transfected with the LCN2 overexpression plasmid vector in vitro. Recombinant human interleukin-17 (IL-17) protein (rhIL-17) at different concentrations was administered to intervene in HPAEpiCs, observing cell viability and analyzing the concentration-dependent effect of IL-17. Results. LCN2 was increased in the alveolar epithelium post-BLM injury, and highly expressed LCN2 was mainly concentrated on AT2 cells in BLM-injured lungs. Meanwhile, LCN2-overexpressing HPAEpiCs showed impaired cell viability and cell growth. HPAEpiC intervention with rhIL-17 mildly rescued the impaired cell proliferation induced by LCN2 overexpression, and the effect of IL-17 intervention was partially concentration-dependent. Conclusions. The results revealed the reversed effect of IL-17 on the impaired proliferative capacity of the alveolar epithelium induced by LCN2 overexpression. The target alveolar epithelial cells regulated by this process were AT2 cells, providing new clues for alveolar epithelium repair after injury and the treatment of lung injury diseases.